The Historicity of the Neronian Persecution: A Response to Brent Shaw - Jones, Christopher P. (New Testament studies, 2017)
Brent Shaw has recently argued that the Neronian persecution never occurred. In fact, there are no grounds for doubting Tacitus' report of the persecution. Sources later than Tacitus (Melito, Dionysius of Alexandria) date the martyrdoms of Peter and Paul to the reign of Nero, but those reports have no bearing on the veracity of Tacitus' account.